Evaluación de la gestión enfermera de la demanda en atención primaria - Brugués Brugués, Alba (Aten Primaria, 2016)
OBJECTIVE: to evaluate the health outcomes of nurse demand management on unscheduled patients in a Primary Care Centre, following a clinical guide designed by the whole primary care team. DESIGN: Cross-sectional study. SETTING: A primary care team from Castelldefels. Barcelona, Spain. PARTICIPANTS: A random sample of 558 patients requesting a consultation for the same day in a Primary Care setting, attended between May 1(st), 2011 and January 31(st), 2012. INTERVENTION: The guide includes 23 health problems that can be dealt by a nurse autonomously, 18 of them possibly requiring an emergency intervention, and shared decision with the physician. Each health problem is divided into three sections: a) a brief definition of the problem; b) an intervention algorithm; and c) nursing diagnoses of North American Nursing Diagnosis Association for each health problem and a description of the possible nursing interventions. RESULTS: We studied 558 patients with a mean age of 42.5 years old (SD 17.7). The most commonly consulted problems were upper respiratory tract symptoms (19.4%), followed by nausea/vomiting (16.5%), and burns/wounds (12.5%). 73.3% of the problems were resolved autonomously by a nurse. 65,8% of the patients attended received health advice. DISCUSSION: Nurse demand management has shown to be highly effective at handling the conditions attended, while it provides a high percentage of health advice and education during consultations